Wear Performance Of Concrete Mixture Paddles With Hardened Surfaces. - Chiong, Kung Kwong (2003)
Throughout this investigation, paddles from the SIMEM concrete mixer plant were selected as the subject for this wear analysis. The numbers of paddles studied are twenty. The performance and wear progress of the paddles were monitored periodically. In this project, six types of hard facing alloy were welded onto the same base metal, cast manganese materials. Hard surfacing is an effective method of modifying the surface properties without changing the whole materials of the paddle. These hard-facing alloys (severe wear resistant and moderate impact resistance characteristics) were welded onto the surfaces and edges of each paddle respectively (each hard facing alloys on three paddles). These welds were as cross lines of 20 mm apart all over the top surface of each paddle and full weld on the front side edges for maximum wear protection. Each weld bead deposited is 3 to 4mm thick and 5 to 6mm wide.Two paddles were selected without any hard facing protective layers in this analysis as a reference purpose. Hard facing alloys used in this research are high Chromium high Carbon alloys (Paddles AI, A2, A3, A4, A5, A6, A7, A9, A11), Complex Chromium Carbide alloys with Boron (Paddles B1 , B2, B3, B4, B5 and B6) and Tungsten Carbide material on paddle B7, B9 and B11. The main parameters measured were the side dimensions loss, thickness loss, volume loss and mass loss. Data collection was collected on a monthly basis in order to obtained higher accuracy. Two sets of paddles were used for each type of hard facing. As one set is in the measuring stage, the next set is fitted in the concrete mixer.